Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/cancers14092308
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Tumor Immune Microenvironment during Neoadjuvant Chemotherapy of High-Grade Serous Ovarian Cancer

Abstract: The dynamic changes in the tumor immune microenvironment (TIME) triggered by neoadjuvant chemotherapy (NAC) have not been clearly defined in advanced-stage ovarian cancer. We analyzed the immunologic changes induced by NAC to correlate them with clinical outcomes. We compared the changes in the immune infiltration of high-grade serous carcinoma biopsies before and after NAC via immunohistochemistry (147 paired samples) and whole transcriptome sequencing (35 paired samples). Immunohistochemistry showed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…Previous studies have shown the effect of chemotherapeutic regimens on tumor immune microenvironment, including an increase in infiltration of CD8 + T cells, CD3 + T cells, CD20 + B cells, and PD-1 + cells ( 13 15 , 19 , 20 ). Regulation of tumor-promoting immune suppressors and immune effectors of the immune system might result in the enhanced antitumor activity of immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the effect of chemotherapeutic regimens on tumor immune microenvironment, including an increase in infiltration of CD8 + T cells, CD3 + T cells, CD20 + B cells, and PD-1 + cells ( 13 15 , 19 , 20 ). Regulation of tumor-promoting immune suppressors and immune effectors of the immune system might result in the enhanced antitumor activity of immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Maximal cytoreductive surgery with platinum-based chemotherapy is the standard treatment modality for advanced-stage ovarian cancer . However, despite achieving complete remission after primary treatment, 60% to 80% of patients with advanced-stage ovarian cancer experience relapse . Several new combinations with platinum-based chemotherapy, including targeted agents, antiangiogenic agents, immunotherapy, and intraperitoneal chemotherapy, have been developed to improve survival outcomes …”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, despite achieving complete remission after primary treatment, 60% to 80% of patients with advanced-stage ovarian cancer experience relapse. 4,5 Several new combinations with platinum-based chemotherapy, including targeted agents, antiangiogenic agents, immunotherapy, and intraperitoneal chemotherapy, have been developed to improve survival outcomes. 6 Hyperthermic intraperitoneal chemotherapy (HIPEC) combines intraperitoneal chemotherapy with hyperthermia and maintains a high chemotherapeutic drug concentration in tumor cells and reduces the adverse effects of intraperitoneal catheter-related complications.…”
mentioning
confidence: 99%
“…NACT has been reported to induce changes in immune regulatory signals as well as reprogramming the tumour immune microenvironment 17,18,19 . In our study, NACT resulted in a significant change in the I-O gene expression signatures associated with avoiding immune destruction and tumour promoting inflammation signatures.…”
Section: Immuno-oncology (I-o) and Inflammation Related Gene Signatur...mentioning
confidence: 99%